Dinamika Dakwah Islam dalam Era Digital: Kajian terhadap Strategi Implementasi dan Tantangan yang Dihadapi - Agustriani Muzayanah; Yasser Muda Lubis (El Madani : Jurnal Dakwah dan Komunikasi Islam, 2023)
This paper discusses the strategies and challenges of da'wah in the digital age. Currently, information and communication technology media is developing very rapidly. This of course must be followed by the development of the tools or means of da'wah used. At present da'wah activities are not only carried out by face-to-face methods, but can also be carried out by remote methods using digital media facilities such as internet media and social media. The development of this technology is a big challenge for every Muslim community in carrying out their da'wah activities, because not all of them are able and able to adapt to the development of these technological media. So every Muslim community needs to understand and determine what strategic steps to implement and what challenges Da'wah will face. Strategic steps that every Muslim must have in preaching include enriching himself with scientific insights, prioritizing a critical attitude towards the information received, utilizing advances in information technology as a means of preaching, having high creativity in creating quality da'wah content , and set a good example by prioritizing good ethical values. The challenge of da'wah in the digital age is in the form of the ability to digitize religious books, creating applications that contain religious content based on Android, increasing the number of podcast media that contain religious understanding as a medium for da'wah.